IMMU-28. TARGETING IMMUNOSUPPRESSIVE MYELOID DERIVED SUPPRESSOR CELLS VIA MIF/CD74 SIGNALING AXIS TO ATTENUATE GBM GROWTH. (11th November 2019) - Alban, Tyler; Bayik, Defne; Otvos, Balint; Grabowski, Matthew; Ahluwalia, Manmeet; Bucala, Richard; Vogelbaum, Michael; Lathia, Justin
Abstract: The immunosuppressive microenvironment in glioblastoma (GBM) enables persistent tumor growth and evasion from tumoricidal immune cell recognition. Despite a large accumulation of immune cells in the GBM microenvironment, tumor growth continues, and evidence for potent immunosuppression via myeloid derived suppressor cells (MDSCs) is now emerging. In agreement with these observations, we have recently established that increased MDSCs over time correlates with poor prognosis in GBM, making these cells of interest for therapeutic targeting. In seeking to reduce MDSCs in GBM, we previously identified the cytokine macrophage migration inhibitory factor (MIF) as a possible activator of MDSC function in GBM. Here, using a novel in vitro co-culture system to reproducibly and rapidly create GBM-educated MDSCs, we observed that MIF was essential in the generation of MDSCs and that MDSCs generated via this approach express a repertoire of MIF receptors. CD74 was the primary MIF receptor in monocytic MDSCs (M-MDSC), which penetrate the tumor microenvironment in preclinical models and patient samples. A screen of MIF/CD74 interaction inhibitors revealed that MN-166, a clinically relevant blood brain barrier penetrant drug, which is currently fast tracked for FDA approval, reduced MDSC generation and function in vitro. This effect was specific to M-MDSC subsets expressing CD74, and appeared as reduced downstream pERK signaling and MCP-1 secretion. In vivo, MN-166 was able reduce tumor-infiltrating MDSCs, while conferring a significant increase in survival in the syngeneic glioma model GL261. These data provide proof of concept that M-MDSCs can be targeted in the tumor microenvironment via MN-166 to reduce tumor growth and provide a rationale for future clinical assessment of MN-166 to reduce M-MDSCs in the tumor microenvironment. Ongoing studies are assessing the effects of MDSC inhibition in combination with immune activating approaches, in order to inhibit immune suppression while simultaneously activating the immune system.